New approaches for the detection of invasive fungal diseases in patients following liver transplantation: results of an observational clinical pilot study - Decker, Sebastian; Wilk, Henryk; Schmitt, Felix; Uhle, Florian; Bruckner, Thomas; Zimmermann, Stefan; Mehrabi, Arianeb; Mieth, Markus; Weiss, Karl Heinz; Weigand, Markus A.; Sohn, Kai; Brenner, Thorsten (Langenbeck's archives of surgery, 2019)
Despite antifungal prophylaxis following liver transplantation (LTX), patients are at risk for the development of subsequent opportunistic infections, such as an invasive fungal disease (IFD). However, culture-based diagnostic procedures are associated with relevant weaknesses.
Gesehen am 30.03.2020